Pharmacology aspects during transition and at transfer in patients with epilepsy. (August 2014) - Chiron, Catherine; An, Isabelle
Summary: Contrary to the treatment concerns regarding drug compliance or pregnancy at transition to adulthood, those directly related to epilepsy remain poorly documented. As an initial step to answer this problem, we reviewed the controlled trials of antiepileptic drugs (AEDs) independently performed in adults and children for a given syndrome. Then we reviewed the longitudinal long‐term course in the various epilepsy syndromes. Optimizing AED treatment at adulthood might be beneficial, even after many years of pharmacoresistance. Finally we retrospectively reviewed our personal series of 39 patients with specific pharmacoresistant epilepsy syndromes, who transferred from pediatric to adult care between 2005 and 2012. In 26 of the patients, AEDs were modified and, we reduced seizure frequency in 62% of them, including highly refractory patients. By contrast, AED changes in six controlled patients (for pregnancy anticipation or vigabatrin‐related retinal toxicity) led to severe seizure relapse. Further studies are needed to elaborate guidelines in pharmacoresistant syndromes during transition and after transfer to adult care.